Optimal Design and Implementation of Autonomous Flight System for Quadrotor UAV - CHEN Zhao; NIAN Xiaohong; XIONG Hongyun; ZHOU Wenxiao (Kongzhi Yu Xinxi Jishu)
From the UAV (unmanned aerial vehicle) hardware realization point of view, this paper introduced the composition of an UAV autonomous flight system, and analyzed common problems of parameter identification and test flight process. To ensure the UAV positioning accuracy, height measurement accuracy, visual sensor measurement information and anti-disturbance performance during the experiment, the influence of single sensor measurement on UAV flight performance was analyzed. The measurement accuracy of the system is improved by multi-sensor information fusion, and the autonomous flight control algorithm was designed to improve the system’s ability to suppress external disturbance. The validity of the design was verified by experiments.